2018
DOI: 10.1111/myc.12844
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility of Microsporum spp. and mammalian cells to Eugenia caryophyllus essential oil, eugenol and semisynthetic derivatives

Abstract: Our study indicates an interesting bioactivity of isoeugenol and methylisoeugenol against M. canis, M. gypseum and mammalian cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The differential activity of tested EOs against biofilm, phospholipase and hemolysin may be related to the chemical composition of these EOs. Several studies [44][45][46] show that the major compound of cinnamon bark oil is cinnamaldehyde (52-80%), the main constituent in clove oil is eugenol with concentration ranges from 68 to 88% [21,47,48], for rosemary oil, 1,8-cineole (26.5-27.2%) and α-pinene (19.2-20%) are predominant [21,49], while jasmine oil has 57.3% of 2-phenylthiolane [50]. The EO antifungal activity can often be attributed to the major constituent [44], or from synergistic effects between two or more EO components [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential activity of tested EOs against biofilm, phospholipase and hemolysin may be related to the chemical composition of these EOs. Several studies [44][45][46] show that the major compound of cinnamon bark oil is cinnamaldehyde (52-80%), the main constituent in clove oil is eugenol with concentration ranges from 68 to 88% [21,47,48], for rosemary oil, 1,8-cineole (26.5-27.2%) and α-pinene (19.2-20%) are predominant [21,49], while jasmine oil has 57.3% of 2-phenylthiolane [50]. The EO antifungal activity can often be attributed to the major constituent [44], or from synergistic effects between two or more EO components [29].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that cinnamon and clove oils showed significantly higher efficacy than miconazole against vulvo-vaginal C. albicans isolates [60]. Additionally, clove oil had a promising in vitro activity against the dermatophyte Microsporum spp and showed low toxicity to mammalian cell lines [48]. However, further clinical trials are required to establish EOs-safety, efficacy and the most suitable drug delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…and dermatophytes [31,32]. The report of Pinto et al [33] showed that CO had MICs and MFCs against M. canis and M. gypseum (standard strains) in the range of 0.00625-0.05% w/v. Aiemsaard et al [34] reported MIC and MFC of CO against M. canis and T. mentagrophytes were 0.00002% v/v and 0.00004% v/v, and the MIC and MFC against M. gypseum were 0.00004% v/v.…”
Section: Antifungal Agent Mic Mfcmentioning
confidence: 99%